Depression and self-harm from adolescence to young adulthood in sexual minorities compared with heterosexuals in the UK: a population-based cohort study. (13th November 2019) - Irish, M; Solmi, F; Mars, B; King, M; Lewis, G; Pearson, R M; Pitman, A; Rowe, S; Srinivasan, R; Lewis, G
Abstract: Background: There are few population-based cohort studies of the emergence, development, and persistence of mental health problems in sexual minorities compared with heterosexuals. We compared trajectories of depressive symptoms in sexual-minority adolescents and heterosexual adolescents from when they were aged 10 to 21 years, and examined self-harm at ages 16 and 21 years. Methods: The study included 4828 adolescents born between April 1, 1991, and Dec 31, 1992, from the Avon Longitudinal Study of Parents and Children birth cohort (Bristol, UK) who reported their sexual orientation when aged 16 years. Depressive symptoms were assessed with the short Mood and Feelings Questionnaire at seven timepoints between ages 10 and 21 years. A self-harm questionnaire was completed at ages 16 and 21 years. Analyses were linear multilevel models with growth curves (depressive symptoms), logistic multilevel models (self-harm in the previous year at ages 16 and 21 years), and multinomial regression (lifetime self-harm with and without suicidal intent at age 21 years). Findings: At age 10, depressive symptoms were higher in sexual minorities than in heterosexuals and increased with age to a larger extent. Depressive symptoms increased at each timepoint by 0·31 points in hetereosexuals, and by 0·49 points in sexual minorities. Sexual-minority adolescents were more likely than heterosexual adolescents to report self-harm in the previous year at ages 16 and 21 years, with no evidence that this estimate decreased with age. At aged 21, sexual minorities were more likely to report lifetime self-harm (ie, on at least one previous occasion) with suicidal intent than heterosexuals. Interpretation: Mental health disparities between heterosexuals and sexual minorities are present early in adolescence and increase throughout the school years, persisting to young adulthood. Prevention of these mental health problems and early intervention must be a priority.